Bio‐physical models of marine environments reveal biases in the representation of protected areas. Issue 3 (2nd January 2019) - Roberts, Kelsey E.; Duffy, Grant A.; Cook, Carly N.
Abstract: The significant shortfall in global marine protection targets is likely to continue to drive rapid growth in marine protected areas (MPAs). Systematic conservation planning to fill gaps in marine protection requires sufficient knowledge of both the distribution of biodiversity and the threats to species and ecosystems. Yet such data are lacking for much of the marine environment, creating significant challenges for planning effective marine protection. In the absence of habitat mapping data, critical environmental variables associated with species' distributions can be used to model the spatial distribution of different environments. Although this approach has been used in some jurisdictions to assist MPA planners, the increased availability and resolution of spatial data now provide an opportunity to improve assessments of MPA representation. Capitalizing on advances in spatial data, this study uses a range of biological and physical environmental attributes to model the distribution of Australian marine environments. Given many Australian MPAs were implemented without knowledge of the distribution of species and benthic habitats, this Bio‐physical model is used to assess MPA coverage and equality of protection for Australian marine environments. Results of the Bio‐physical model revealed that Australian MPAs overrepresent warm, offshore waters (such as the Coral Sea) and underrepresent temperate environments. Furthermore, the distribution of protection in Australian MPAs is heavily skewed, with no‐take protection disproportionately targeting tropical environments, leaving major gaps in the protection of both temperate and nearshore habitats. Without comprehensive habitat mapping, the representativeness and adequacy of an MPA system cannot be accurately evaluated, nor can the required expansion of MPAs be planned effectively. In the interim, the biological and physical attributes chosen for this model provide useful proxies to assist in efforts to better target current and future protection based on the most up‐to‐date knowledge.